Financial Constraints on New Firms: Looking for Regional Disparities - Jean Bonnet; Sylvie Cieply; Marcus Dejardin (Max Planck Institute of Economics, 2005)
Financial constraints affecting new firms are some of the factors most cited for impeding entrepreneurial dynamics from flourishing. This article introduces the problem of regional patterns of financial constraints. The research is conducted with regard to the French regions and the new French firms being tracked at the firm level. As regard to new firms, the research relies mainly on the use of the Information System on New Firms (SINE) that is released by the French National Institute of Statistical and Economic Studies (INSEE). The SINE dataset does not refer to the general entrepreneurial intention in the French population but to entrepreneurial projects that are concretized in new firms. As a consequence, entrepreneurial intentions that are aborted due to financial constraints are not reported. The point is of importance as the firm financing conditions are considered. First, an assessment of the global situation of the banking density and activity within and between the French regions leads to the conclusion of a relatively homogeneous banking supply and banking activity, with the activity of the core-region Île-de-France appearing however more contrasted. Second, the financial constraints affecting new firms are distinguished according to a four-case typology. Additionally to the no credit rationing situation, weak or strong credit rationing are distinguished from the self-constraint situation, a situation describing the case when firms do not ask for a bank loan although they declare facing financial constraints subsequently. It appears that a majority of new firms is not facing credit rationing, but also that a non-negligible share is self-constrained. The classification is, third and finally, differentiated according to the regions. Despite the relative homogeneity of the banking supply, it appears that some regional differences may still be at work. The given explanations are still hypothetical at this stage but the empirical results suggest already that the regional dimension should definitely deserve further attention.
Keywords: G20; M13; R10; 330; Financial constraints; Credit rationing; New Firms; Regional Disparities; Tarifvertrag; Lohnpolitik; Lohnstruktur; Zeitlohn; Beschäftigungseffekt; Schätzung; Niedersachsen; Deutschland